Method for improving ductility of high-iron-content A356 alloy

By adding Sr elements to the high-iron content A356 alloy and optimizing the cooling rate, the generation of β-Al5FeSi phase is suppressed, and the problem of low elongation of alloys under high Fe content in the prior art is solved, thereby achieving efficient elongation and cost reduction.

CN119287249APending Publication Date: 2025-01-10SHANGHAI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411398111.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art cannot effectively improve the elongation of high-iron content A356 alloy, and the existing methods increase production costs and process complexity, especially under high Fe content conditions.

Method used

By adding Sr elements to the alloy and reducing the cooling rate, the generation of β-Al5FeSi phase is suppressed, and the composition and solidification path of the alloy are determined by thermodynamic equilibrium phase diagram, the Fe element content and cooling rate are optimized to achieve eutectic Si and Fe-rich Phase refinement improves the elongation of the alloy.

Benefits of technology

The elongation of the alloy under high Fe content has been achieved, with an elongation of 6.02%, while the process flow has been simplified and production costs have been reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287249A_ABST
    Figure CN119287249A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the elongation of a high-iron-content A356 alloy, which comprises the following steps of: firstly, obtaining or retrieving data of a thermodynamic database of an existing Al-Si-Mg-Fe system through an experiment; then, obtaining a thermodynamic equilibrium phase diagram by adopting a thermodynamic calculation method; and finally, determining a solidification path according to the thermodynamic equilibrium phase diagram, and determining the value range of the Fe element content. In the A356 alloy, the content of Fe is 0.5 wt.%, the content of Sr is 0.02 wt.%, and the cooling rate is 2 DEG C / s. The specific method comprises the following steps: 1, preparing an Al-7Si-0.3 Mg-0.5 Fe alloy melt; and 2, preparation of the Al-7Si-0.3 Mg-0.5 Fe-0.02 Sr alloy is carried out. The preparation method comprises the following In the obtained high-iron-content A356 alloy, the length of eutectic Si is 20.00 [mu] m, and the length of an Fe-rich phase is 55.70 [mu] m; and the ductility of the alloy is 6.02%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nonferrous metal materials and metallurgy, and in particular to a method for improving the elongation of an A356 alloy with a high iron content. Background Art

[0002] A356 alloy has the characteristics of high specific strength, good castability, strong machinability and excellent corrosion resistance. It is widely used in aerospace, automobile industry, shipbuilding and other fields, and is the preferred material for automobile wheels. However, the energy consumption of industrial electrolytic production of A356 is high. Therefore, in order to solve the problem of high energy consumption in the industrial production of A356 alloy, recycled A356 alloy can be obtained by recycling waste aluminum alloy materials. The energy required for the production process of recycled aluminum is only 5% of that of electrolytic aluminum. The production of recycled A356 alloy can greatly reduce the energy consumption of industrial production. However, the impurity Fe element that is difficult to remove in the recycled A356 alloy will seriously reduce the elongation of the alloy. The impurity Fe will form a needle-shaped β-Al5FeSi phase in the alloy, which is seriously harmful to the elongation of the alloy. Under the action of tensile load, the hard and brittle needle-shaped β-Al5FeSi phase will cause stress concentration, and microcracks often initiate from these particles and provide a path for the expansion of macro cracks, thereby significantly reducing the elongation of the alloy. In addition, the needle-like β-Al5FeSi phase will hinder the melt flow and increase defects such as shrinkage and shrinkage, which will also have an adverse effect on the ductility of the alloy. If the iron content increases from 0.15wt.% to 0.90wt.%, the elongation of the aluminum alloy will decrease by 47%.

[0003] At present, in the process of improving the elongation of A356 alloy, many technical solutions have added more process flows just to improve the elongation performance, which leads to an increase in the cost of the entire technical solution. For example, in the existing document 1 (Effect of Holding Pressure on Microstructure and Mechanical Properties of A356 Aluminum Alloy [J]. Journal of Materials Engineering and Performance, 2018, 27 (2): 483-491.), the casting pressure of A356 alloy is increased from 85kPa to 300kPa, and the alloy is subjected to T6 heat treatment to reduce the secondary dendrite arm spacing of the alloy from 50.7μm to 39.2μm, so that the elongation of the alloy is increased from 2.8% to 9.1%. As mentioned above, although the technical solution makes the alloy elongation exceed 6%, the necessary technical feature of the technical solution uses a die-casting machine, that is, there is a technical problem of high equipment requirements. In addition, the material obtained by the technical solution also needs to be heat treated, and this necessary technical feature also significantly and directly increases the production process and production time.

[0004] For example, in the existing document 2 (Microstructure and Mechanical Properties of Friction Stir Processed A356 Cast Al under Air Cooling and Water Cooling [J]. High Temperature Materials and Processes, 2017, 37 (7) 1-7.), the cast A356 alloy was subjected to friction stir processing. After the alloy underwent strong plastic deformation, the average grain size was reduced from 230 μm to 6 μm, and the elongation was increased from 1.30% to 8.11%. This technical solution also has the problem that in order to improve the elongation of the alloy, new process operations and equipment must be introduced, which directly leads to an increase in production costs.

[0005] It can be seen from existing documents 1 and 2 that the technical solutions for improving the elongation of alloys based on heat treatment or mechanical processing inevitably increase the complexity of the process and increase the production cost. After comprehensively considering reducing costs and simplifying processes, the commonly used methods for improving the elongation of alloys in the industry can be divided into two categories:

[0006] 1. Optimize the alloy composition. Adding the modified element Sr can adjust the phase type and morphology. The reason is that the Sr element can form Al2Si2Sr phase in the A356 alloy. Al2Si2Sr will be enriched at the growth front of eutectic silicon, inhibiting the growth of eutectic Si, achieving the refinement of eutectic Si, and thus improving the elongation of the alloy;

[0007] 2. Adjust the preparation process. Increasing the cooling rate can increase the degree of supercooling, increase the nucleation rate, and increase the number of nuclei, thereby inhibiting the growth space of various phases in the alloy and achieving phase refinement. In addition, increasing the cooling rate will also increase the temperature gradient, reduce the diffusion time of solute elements, inhibit the growth of phases, and achieve the purpose of improving the elongation of the alloy.

[0008] The elongation of the alloy can be improved by adding the modified element Sr to regulate the phase type and morphology. For example, the existing document 3 (Effect of Refinement and Modification on Microstructure, Properties and Eutectic Silicon Growth Mechanism of Cast A356 Aluminum Alloy [J]. Rare Metal Materials and Engineering, 2020, 49 (8): 2665-2673.) reduces the size of eutectic Si in A356 alloy from 40-60 μm to below 10 μm by adding 0.03 wt.% Sr, and the elongation increases from 1.17% to 5.70%. Although this technical solution achieves the technical effect of refining eutectic Si and improving the elongation of the alloy by adding Sr elements, the applicable conditions of this technical solution are that the Fe content in the alloy is only 0.17 wt.%, and at the same time, the Fe-rich phase size is less than 20 μm. According to common knowledge in the art, as the Fe content increases, the size of the Fe-rich phase also increases significantly, which directly leads to a significant decrease in the elongation of the alloy. That is, this technical solution cannot solve the problem of improving the elongation of the alloy under high Fe content conditions.

[0009] For example, in the existing document 4 (On influence of Ti and Sr on microstructure, mechanical properties and quality index of cast eutectic Al-Si-Mg alloy [J]. Materials and Design, 2011, 32 (4): 1865-1871.), the eutectic Si size in the Al-12Si-3Cu-0.44Fe alloy is reduced from 81 μm to 42 μm by adding 0.03 wt.% Sr, and the alloy elongation is only increased from 2.7% to 4.7%. This technical solution has the same technical problem as the existing document 3, which is specifically reflected in that in this technical solution, the Fe content of the alloy is 0.44 wt.%, and the Fe-rich phase size can reach 150 μm. The substantial increase in the size of the Fe-rich phase greatly weakens the improvement effect of adding the Sr element on the alloy elongation.

[0010] It can be seen from the above-mentioned prior art that although the addition of Sr elements can improve the elongation of the alloy by refining the eutectic Si, when the Fe content of the alloy exceeds 0.2wt.%, the size of the Fe-rich phase in the alloy will increase significantly, and the improvement effect of adding Sr elements on the elongation of the alloy will be inhibited.

[0011] Similarly, the effect of increasing the cooling rate on improving the elongation of the alloy will also be inhibited by the high Fe content in the alloy. For example, existing document 5 (A study of tensile properties in Al-Si-Cu and Al-Si-Mgalloys: Effect of β-iron intermetallics and porosity [J]. Materials Science and Engineering A, 2008, 37 (490): 36-51.) increased the cooling rate from 0.22 ° C / s to 10.5 ° C / s, which reduced the Fe-rich phase size in the A356 alloy from 213 μm to 29 μm, and increased the elongation from 0.5% to 5.4%. However, in this technical solution, the Fe content in the alloy is only 0.12wt.%, and it is also impossible to improve the elongation of the alloy under the condition of high Fe content.

[0012] When the Fe content in the alloy is higher than 0.2wt.%, the effect of increasing the cooling rate on improving the elongation of the alloy will be significantly reduced. For example, in the existing document 6 (Microstructure, tensile and fatigue properties of the Al-10%Si-2%Cu alloy with different Fe and Mn content cast under controlled conditions [J]. Journal of Materials Processing Technology, 2009, 35 (15-16): 5669-5679.), by increasing the cooling rate from 1°C / s to 130°C / s, the Fe-rich phase in the Al-10Si-2Cu-0.5Fe alloy can be reduced from 120μm to 20μm, but the elongation of the alloy is only slightly increased from 0.9% to 3.4%.

[0013] For example, the existing document 7 (Effect of Cooling Rate on the Microstructure Evolution and Mechanical Properties of Iron-Rich Al-Si Alloy, 2022, 15(411): 1-10.) can also reduce the Fe-rich phase in the Al-10Si-1.5Fe alloy from 80 μm to 10 μm by increasing the cooling rate from 10°C / s to 670°C / s. However, the elongation of the alloy is only slightly increased from 3.4% to 4.9%.

[0014] Therefore, it can be seen from existing documents 6 and 7 that even if the cooling rate is greatly increased to 130°C / s and 670°C / s, respectively, and the technical effect of reducing the size of the Fe-rich phase to 20μm and 10μm, respectively, is obtained, the elongation of the alloy does not exceed 5%, that is, the existing technology cannot solve the technical problem of improving the elongation of the alloy under high Fe content conditions by increasing the cooling rate.

[0015] Further in-depth analysis of the technical problems of existing documents 6 and existing documents 7 shows that even if the cooling rate is increased to a very high cooling rate, that is, after greatly increasing the production requirements and production difficulty, the technical effect improvement is not achieved accordingly. After research, the inventors believe that the reasons leading to the above problems can be simply summarized as follows: increasing the cooling rate will not only refine the structure, but also lead to the formation of needle-shaped β-Al5FeSi phase, and as the cooling rate is further increased, the supercooling will increase, the nucleation driving force of the β-Al5FeSi phase will also increase significantly, and the nucleation rate will increase significantly; and the β-Al5FeSi phase is a typical non-equilibrium phase, that is, when the cooling rate is low, there is more time to adjust the phase structure and form an equilibrium phase, thereby reducing the negative impact on the elongation, and under high cooling rate conditions, the formation of non-equilibrium phases dominates, and the β-Al5FeSi phase cannot be adjusted to an equilibrium phase after it is generated, which leads to a significant increase in the number of nuclei of the needle-shaped β-Al5FeSi phase despite the reduction in the size of the β-Al5FeSi phase, which ultimately leads to a significant increase in the negative impact on the elongation of the alloy, that is, when the cooling rate is greatly increased, the elongation improvement effect is not significant. Summary of the invention

[0016] The purpose of the present invention is to provide a method for improving the elongation of high iron content A356 alloy. In view of the existing technical problems, the basic principles involved in the present invention are:

[0017] 1. When Sr element is added, Al2Si2Sr phase will be generated preferentially relative to eutectic Si in the alloy. Therefore, Al2Si2Sr phase will be enriched at the growth front of eutectic Si, thereby inhibiting the growth of eutectic Si, achieving the purpose of refining eutectic Si, and finally achieving the effect of improving the elongation of the alloy;

[0018] 2. Increasing the cooling rate can not only achieve the conventional effect of increasing supercooling, promoting the increase of nucleation rate, increasing the number of nucleations, and then inhibiting the growth space of the phase, and achieving the technical effect of refining the phase, but also increase the temperature gradient, reduce the diffusion time of solute elements, inhibit the growth of the phase, and then refine the phase and improve the elongation of the alloy.

[0019] At the same time, according to the inventor's research, it was found that:

[0020] 1. Adding Sr element at a low cooling rate (2℃ / s) can effectively inhibit the formation of β-Al5FeSi phase and promote the improvement of alloy elongation;

[0021] 2. At the same time, under the condition of low cooling rate, Sr element can be fully diffused in the alloy, and then segregated at the grain boundary, effectively covering or segregating at the nucleation position, changing the interface energy between the liquid phase and the solid phase, increasing the nucleation energy barrier of the β-Al5FeSi phase, and thus inhibiting its formation;

[0022] 3. In addition, when the cooling rate is low, the Sr element can effectively promote the nucleation and growth of the Chinese character-shaped α-Al8Fe2Si phase, which has no harm to the alloy properties. This reduces the Fe content in the melt, thereby indirectly inhibiting the formation of the needle-shaped β-Al5FeSi phase, which has great harm to the alloy properties.

[0023] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0024] A method for improving the elongation of an A356 alloy with a high iron content, firstly, obtaining or retrieving data from an existing Al-Si-Mg-Fe system thermodynamic database through experiments; then, using a thermodynamic calculation method to obtain a thermodynamic equilibrium phase diagram of the Al-Si-Mg-Fe alloy within a certain temperature range; finally, determining the solidification path of the alloy that produces different forms of β-Al5FeSi phases according to the thermodynamic equilibrium phase diagram, and determining the value range of the Fe element content according to application requirements;

[0025] The composition of the Al-Si-Mg-Fe alloy is Al-7Si-0.3Mg-xFe alloy (0≤x≤3);

[0026] The temperature range of the thermodynamic equilibrium phase diagram is 500-700°C;

[0027] The solidification path of the Al-7Si-0.3Mg-xFe alloy (0≤x≤3) in the range of 500-700°C is specifically divided into the following three cases:

[0028] When the Fe content is in the range of 0-0.17wt.%, the solidification paths are L→α-Al, L→α-Al+Si and L→α-Al+Si+β-Al5FeSi;

[0029] When the Fe content is in the range of 0.17-1.09wt.%, the solidification paths are L→α-Al, L→α-Al+β-Al5FeSi and L→α-Al+Si+β-Al5FeSi;

[0030] When the Fe content is in the range of 1.09-1.65wt.%, the solidification paths are L→β-Al5FeSi, L→α-Al+β-Al5FeSi and L→α-Al+Si+β-Al5FeSi;

[0031] The composition of the A356 alloy is Al-7Si-0.3Mg, and the Fe content of the A356 alloy is 0.5wt.%, the Sr content is 0.02wt.%, and the cooling rate is 2°C / s.

[0032] A method for improving the elongation of high iron content A356 alloy, comprising the following steps:

[0033] Step 1, preparation of Al-7Si-0.3Mg-0.5Fe alloy melt, with Al-7Si-0.3Mg alloy and Al-20Fe alloy satisfying a certain mass ratio, firstly, heating and melting the Al-7Si-0.3Mg alloy under a certain heating temperature condition to obtain an Al-7Si-0.3Mg alloy melt, referred to as AlSiMg alloy melt, then, adding Al-20Fe into the AlSiMg alloy melt and completely melting it, to obtain an Al-7Si-0.3Mg-0.5Fe alloy melt, referred to as AlSiMgFe-0.5 alloy melt;

[0034] In the step 1, the mass ratio of Al-7Si-0.3Mg alloy to Al-20Fe alloy is 1:0.026, and the heating temperature for obtaining the Al-7Si-0.3Mg alloy melt is 800° C.;

[0035] Step 2, preparation of Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy, first, the AlSiMgFe-0.5 alloy melt obtained in step 1 is cooled to a certain temperature in the furnace, then Al-10Sr is added to the AlSiMgFe-0.5 alloy melt to meet a certain addition amount of Al-10Sr, to obtain Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy melt, referred to as AlSiMgFeSr-0.5 alloy melt, then, under certain conditions, The AlSiMgFeSr-0.5 alloy melt is kept warm, and then, under certain conditions, high-purity argon gas is introduced into the AlSiMgFeSr-0.5 alloy melt, and at the same time, the mold is preheated. Finally, the AlSiMgFeSr-0.5 alloy melt is cast into the mold, and the AlSiMgFeSr-0.5 alloy melt is cooled at a certain cooling rate to obtain an Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy, referred to as AlSiMgFeSr-0.5;

[0036] In the step 2, the temperature of the Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy melt is 740°C, the addition amount of Al-10Sr is 0.2wt.%, and the holding temperature is 740°C for 40 minutes;

[0037] The conditions for the introduction of high-purity argon gas are as follows: the ventilation rate is 0.25 L / min and the ventilation time is 3 min;

[0038] The cooling rate is 2°C / s;

[0039] The method for achieving a cooling rate of 2°C / s is that the preheating temperature of the mold is 400°C.

[0040] In the obtained high iron content A356 alloy, the length of eutectic Si is 20.00 μm, the length of Fe-rich phase is 55.70 μm; and the elongation of the alloy is 6.02%.

[0041] The technical effects of the present invention have been tested experimentally, and the specific contents are as follows:

[0042] Through phase diagram calculation, it is determined that when the Fe content is greater than 0.17wt.%, the needle-shaped β-Al5FeSi phase will be generated in the form of a binary eutectic structure of α-Al+β-Al5FeSi. At this time, the needle-shaped β-Al5FeSi phase is larger in size, which has a greater impact on the elongation of the alloy. When the Fe content is greater than 1.09wt.%, a primary β-Al5FeSi phase will be formed. At this time, the size of the β-Al5FeSi phase will be very large, which will further increase the damage to the elongation of the alloy.

[0043] By quantitatively counting the sizes of eutectic Si and Fe-rich phases in the metallographic diagram, it is proved that adding Sr can refine the eutectic Si, and increasing the cooling rate can reduce the size of the Fe-rich phase. Moreover, when the Sr addition amount is 0.02wt.%, the Fe content is 0.5wt.%, and the cooling rate is 2℃ / s, the sizes of eutectic Si and β-Al5FeSi phases in Al-7Si-0.3Mg alloy are 20.00μm and 55.70μm respectively.

[0044] The effect of increasing elongation by adding Sr was shown in the mechanical property test. When the cooling rate was 2°C / s, the addition of 0.02wt.% Sr increased the elongation of the Al-7Si-0.3Mg alloy with a Fe content of 0.5wt.% from 2.92% to 6.02%.

[0045] The effect of increasing the cooling rate to improve the elongation was shown in mechanical property tests. When 0.02wt.% Sr was added, the cooling rate was increased from 0.4℃ / s to 2℃ / s, and the elongation of the Al-7Si-0.3Mg alloy with an Fe content of 0.5wt.% increased from 2.87% to 6.02%.

[0046] Compared with the prior art, the present invention has the following advantages:

[0047] 1. For Al-7Si-0.3Mg alloy with an Fe content of 0.5wt.%, the elongation of the alloy can be increased to 6.02% by increasing its cooling rate from 0.4℃ / s to 2℃ / s and adding 0.02wt.% Sr, while other literatures have not yet achieved an elongation of 6% for Al-7Si-0.3Mg alloy with an Fe content of 0.5wt.% by only increasing the cooling rate and adding Sr;

[0048] 2. The present invention only needs to add 0.02wt.% Sr to the raw materials and slightly increase the cooling rate of the alloy by changing the preheating temperature of the casting mold to make the alloy elongation reach 6.02%. There is no need to change other production process flows of the alloy, nor is there any need to add complex and costly operations such as heat treatment and mechanical processing. Compared with other technologies for improving the elongation of the alloy, the cost is low and the implementation is convenient.

[0049] Therefore, compared with the prior art, the present invention has a simple operation process and the alloy has a higher elongation after adding Sr and increasing the cooling rate, which meets the application requirements and production requirements and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 The thermodynamic equilibrium phase diagram of Al-7Si-0.3Mg-xFe (0≤x≤3) alloy at 500-700℃;

[0051] Figure 2 This is the OM test diagram of Example 1;

[0052] Figure 3 This is the tensile test diagram of Example 1;

[0053] Figure 4 This is the OM test diagram of Comparative Example 1;

[0054] Figure 5 This is the tensile test diagram of Comparative Example 1;

[0055] Figure 6 This is the OM test diagram of Comparative Example 2;

[0056] Figure 7 This is the tensile test diagram of Comparative Example 2;

[0057] Figure 8 This is the OM test diagram of Comparative Example 3;

[0058] Fig. 9 This is the tensile test diagram of Comparative Example 3. DETAILED DESCRIPTION

[0059] The present invention is further described in detail through embodiments and comparative examples in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0060] Based on the data from the Al-Si-Mg-Fe system thermodynamic database, the thermodynamic equilibrium phase diagram of Al-7Si-0.3Mg-xFe alloy (0≤x≤3) in the range of 500-700℃ was obtained by thermodynamic calculation method. Figure 1 As shown in Figure 2, the solidification path of Al-7Si-0.3Mg alloy is affected by the Fe content, specifically,

[0061] When the Fe content is in the range of 0-0.17wt.%, the solidification paths are L→α-Al, L→α-Al+Si and L→α-Al+Si+β-Al5FeSi, among which β-Al5FeSi, as a part of the α-Al+Si+β-Al5FeSi eutectic structure, has the characteristics of small size, so the negative impact on the alloy properties can be ignored;

[0062] When the Fe content is in the range of 0.17-1.09wt.%, the solidification paths are L→α-Al, L→α-Al+β-Al5FeSi and L→α-Al+Si+β-Al5FeSi. At this time, there is β-Al5FeSi generated in the form of a binary eutectic structure of α-Al+β-Al5FeSi. The size of the β-Al5FeSi formed based on this solidification path is larger than that of the β-Al5FeSi phase in the α-Al+Si+β-Al5FeSi eutectic structure. Therefore, the negative impact on the alloy properties is prominent, that is, it cannot be ignored.

[0063] When the Fe content is in the range of 1.09-1.65wt.%, β-Al5FeSi phase is generated as the primary phase. The size of β-Al5FeSi formed based on this solidification path is larger than that of β-Al5FeSi phase formed in the first two cases. Therefore, it has a significant negative impact on the alloy properties.

[0064] In order to facilitate the distinction between various alloys and their basic information involved in various embodiments and comparative examples, Table 1 is provided.

[0065] Table 1 Summary of alloy composition and cooling rate of embodiments and comparative examples

[0066] Alloy composition (wt.%) Cooling rate (℃ / s) Example 1 Al-7Si-0.3Mg-0.5Fe-0.02Sr 2 Comparative Example 1 Al-7Si-0.3Mg-0.5Fe 2 Comparative Example 2 Al-7Si-0.3Mg-0.5Fe-0.02Sr 0.4 Comparative Example 3 Al-7Si-0.3Mg-1.1Fe-0.02Sr 2

[0067] Example 1

[0068] A method for improving the elongation of high iron content A356 alloy, comprising the following steps:

[0069] Step 1, preparation of Al-7Si-0.3Mg-0.5Fe alloy melt, with the mass ratio of Al-7Si-0.3Mg alloy to Al-20Fe alloy being 1:0.026, firstly, heating and melting the Al-7Si-0.3Mg alloy at a heating temperature of 800°C to obtain an Al-7Si-0.3Mg alloy melt, referred to as AlSiMg alloy melt, then adding Al-20Fe into the AlSiMg alloy melt and completely melting it to obtain an Al-7Si-0.3Mg-0.5Fe alloy melt, referred to as AlSiMgFe-0.5 alloy melt;

[0070] Step 2, preparation of Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy, first, the AlSiMgFe-0.5 alloy melt obtained in step 1 is cooled to 740°C in the furnace, then, Al-10Sr is added to the AlSiMgFe-0.5 alloy melt in an amount of 0.2wt.%, to obtain Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy melt, referred to as AlSiMgFeSr-0.5 alloy melt, then, the AlSiMgFeSr-0.5 alloy melt is heated at a holding temperature of 740°C for 40min. The alloy melt is kept warm, and then high-purity argon is introduced into the AlSiMgFeSr-0.5 alloy melt at a ventilation rate of 0.25 L / min for 3 min. At the same time, in order to achieve a cooling rate of 2 ° C / s, the mold is preheated at a preheating temperature of 400 ° C. Finally, the AlSiMgFeSr-0.5 alloy melt is cast into the mold and cooled at a cooling rate of 2 ° C / s to obtain Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy, referred to as AlSiMgFeSr-0.5.

[0071] In order to prove and quantify the size of eutectic Si and Fe-rich phases in AlSiMgFeSr-0.5, OM test was carried out to quantitatively count the size of eutectic Si and Fe-rich phases. The specific method of OM test is that the magnification of metallographic images is 500 times, the number of metallographic images is 10, the length of the largest 10 eutectic Si and Fe-rich phases is counted, and the average value is calculated as the length of eutectic Si and Fe-rich phases. The test results are shown in Figure 2 As shown in Table 2, in AlSiMgFeSr-0.5, the eutectic Si length is 20.00 μm and the Fe-rich phase length is 55.70 μm.

[0072] Table 1 Summary of the sizes of eutectic Si and Fe-rich phases and alloy elongation in the alloys of the embodiments and comparative examples

[0073] Eutectic Si length (μm) Fe-rich phase length (μm) Elongation(%) Example 1 20.00 55.70 6.02 Comparative Example 1 50.40 62.15 2.92 Comparative Example 2 27.74 96.61 2.87 Comparative Example 3 22.34 117.80 2.76

[0074] In order to prove the elongation of AlSiMgFeSr-0.5, a tensile test was conducted. The specific parameters of the tensile test are: the total length of the tensile rod is 160mm, the gauge section diameter is 10mm, the clamping section diameter is 12mm, the tensile rate is 1mm / min, the number of parallel tests is 3 times, and the average value of the 3 test results is taken as the elongation of the alloy. The tensile test results are shown in Figure 3 As shown in Table 2, the elongation of AlSiMgFeSr-0.5 is 6.02%.

[0075] In order to demonstrate the effect of adding Sr element on elongation, comparative example 1 is provided, which is an Al-7Si-0.3Mg-0.5Fe alloy without adding Sr.

[0076] Comparative Example 1

[0077] A method for preparing a high-Fe content A356 alloy without adding Sr, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 2, the Sr element is not introduced, that is, Al-10Sr is not added, so that an Al-7Si-0.3Mg-0.5Fe alloy without adding Sr can be obtained, which is referred to as AlSiMgFe-0.5 for short.

[0078] In order to verify the size of eutectic Si and Fe-rich phases in AlSiMgFe-0.5, OM test was performed. The test results are shown in Figure 4 As shown in Table 2, in AlSiMgFe-0.5, the length of eutectic Si is 50.40 μm, and the length of Fe-rich phase is 62.15 μm. Compared with Example 1, although the addition of Sr element can only slightly reduce the size of Fe-rich phase, it can significantly reduce the size of eutectic Si by 39.68%.

[0079] In order to prove the elongation of AlSiMgFe-0.5, a tensile test was carried out. The test results are shown in Figure 5 As shown in Table 2, the elongation of AlSiMgFe-0.5 is 2.92%. Compared with Example 1, it can be seen that the addition of Sr element can significantly increase the elongation, and the increase reaches 206.16%.

[0080] By comparing Comparative Example 1 with Example 1, it can be seen that the addition of Sr increases the elongation by reducing the size of eutectic Si, and the elongation is inversely proportional to the reduction of the size of eutectic Si by adding Sr.

[0081] In order to demonstrate the effect of cooling rate on elongation, Comparative Example 2 is provided, in which an Al-7Si-0.3Mg-0.5Fe alloy is prepared at a cooling rate of 0.4°C / s.

[0082] Comparative Example 2

[0083] A method for preparing a high-Fe content A356 alloy with a cooling rate of 0.4°C / s, wherein the steps not specifically described are the same as those in Example 1, except that: in step 2, in order to achieve a cooling rate of 0.4°C / s, the mold is preheated at a preheating temperature of 500°C, and an Al-7Si-0.3Mg-0.5Fe alloy with a cooling rate of 0.4°C / s can be obtained, which is referred to as AlSiMgFeSr-0.5-Slow.

[0084] In order to verify the size of eutectic Si and Fe-rich phases in AlSiMgFeSr-0.5-Slow, OM test was performed. The test results are shown in Figure 6 As shown in Table 2, in AlSiMgFeSr-0.5-Slow, the length of eutectic Si is 27.74 μm, and the length of Fe-rich phase is 96.61 μm. Compared with Example 1, although increasing the cooling rate can only slightly reduce the size of eutectic Si, it can significantly reduce the size of Fe-rich phase by 57.65%.

[0085] In order to prove the elongation of AlSiMgFeSr-0.5-Slow, tensile tests were performed. The test results are shown in Figure 7 As shown in Table 2, the elongation of AlSiMgFeSr-0.5-Slow is 2.87%. Compared with Example 1, it can be seen that increasing the cooling rate can significantly increase the elongation, and the increase reaches 209.76%.

[0086] By comparing Comparative Example 2 with Example 1, it can be seen that increasing the cooling rate increases the elongation by reducing the size of the Fe-rich phase, and the elongation is inversely proportional to the increase in cooling rate to reduce the size of the Fe-rich phase.

[0087] By comparing Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that adding Sr and increasing the cooling rate can both increase the elongation, but the action mechanisms of the two technical features are different, that is, they cannot replace each other.

[0088] In order to demonstrate the effect of Fe content on elongation, Comparative Example 3 is provided, which shows the effect of adding Sr element on the elongation of Al-7Si-0.3Mg alloy when the Fe content is as high as 1.1 wt.%.

[0089] Comparative Example 3

[0090] A method for preparing an A356 alloy with an Fe content of 1.1wt.%, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 1, the mass ratio of the Al-7Si-0.3Mg alloy to the Al-20Fe alloy is 1:0.058, and the step 1 can obtain an Al-7Si-0.3Mg-1.1Fe alloy melt, referred to as the AlSiMgFe-1.1 alloy melt, and the step 2 can obtain an Al-7Si-0.3Mg-1.1Fe-0.02Sr alloy, referred to as AlSiMgFeSr-1.1.

[0091] In order to verify the size of eutectic Si and Fe-rich phases in AlSiMgFeSr-1.1, OM test was performed. The test results are shown in Figure 8 As shown in Table 2, in AlSiMgFeSr-1.1, the length of eutectic Si is 22.34 μm, and the length of Fe-rich phase is 117.80 μm. Compared with Example 1, when the Fe content is 1.1 wt.%, adding Sr element can reduce the size of eutectic Si to a range close to that of Example 1, but since the content of Fe element increases to 220.00% of that of Example 1, the size of Fe-rich phase also increases by 211.49%.

[0092] In order to prove the elongation of AlSiMgFeSr-1.1, tensile tests were carried out. The test results are shown in Fig. 9 As shown in Table 2, the elongation of AlSiMgFeSr-1.1 is 2.76%. Compared with Example 1, when the Fe content is reduced to 0.5wt.%, the elongation of the Al-7Si-0.3Mg alloy can be significantly improved, and the improvement reaches 218.12%.

[0093] By comparing Comparative Example 3 with Example 1, it can be seen that when the Fe content is as high as 1.1wt.%, the addition of Sr element can also significantly reduce the size of eutectic Si, that is, the Fe content does not affect the effect of adding Sr element to reduce the size of eutectic Si; at the same time, the size of the Fe-rich phase is the same as the increase in the Fe content, that is, the size of the Fe-rich phase is in direct proportional function with the Fe content, and it can be further inferred that the elongation is in inverse proportional function with the Fe content.

[0094] Combined with the actual application requirements for elongation, it can be determined:

[0095] When the Fe content reaches 1.1wt.%, even if Sr is added and the cooling rate is increased, the elongation of the alloy is still very low, only 2.76%, which cannot meet the application requirements;

[0096] When the Fe content is 0.5wt.%, without Sr or at a low cooling rate, the alloy elongation is less than 3%, which also cannot meet the application requirements;

[0097] When the Fe content is 0.5wt.%, adding Sr and increasing the cooling rate can significantly increase the alloy elongation to 6.02%, meeting the application requirements.

[0098] Therefore, the Fe content in the Al-7Si-0.3Mg alloy should be lower than 0.5 wt.%, and the method to improve the elongation must simultaneously add Sr and increase the cooling rate.

Claims

1. A method for improving the elongation of high iron content A356 alloy, characterized in that: First, the data of the existing Al-Si-Mg-Fe system thermodynamic database are obtained experimentally or retrieved; Then, the thermodynamic equilibrium phase diagram of Al-Si-Mg-Fe alloy within a certain temperature range is obtained by thermodynamic calculation method; Finally, the solidification paths of alloys that produce different forms of β-Al5FeSi phases are determined based on the thermodynamic equilibrium phase diagram, and the value range of Fe content is determined based on application requirements; The composition of the Al-Si-Mg-Fe alloy is Al-7Si-0.3Mg-xFe alloy (0≤x≤3); The temperature range of the thermodynamic equilibrium phase diagram is 500-700°C.

2. The method according to claim 1, characterized in that: The solidification path of the Al-7Si-0.3Mg-xFe alloy (0≤x≤3) in the range of 500-700°C is specifically divided into the following three cases: When the Fe content is in the range of 0-0.17wt.%, the solidification paths are L→α-Al, L→α-Al+Si and L→α-Al+Si+β-Al5FeSi; When the Fe content is in the range of 0.17-1.09wt.%, the solidification paths are L→α-Al, L→α-Al+β-Al5FeSi and L→α-Al+Si+β-Al5FeSi; When the Fe content is in the range of 1.09-1.65wt.%, the solidification paths are L→β-Al5FeSi, L→α-Al+β-Al5FeSi and L→α-Al+Si+β-Al5FeSi.

3. The method according to claim 1, characterized in that: The composition of the A356 alloy is Al-7Si-0.3Mg, and the Fe content in the A356 alloy is 0.5wt.%.

4. The method according to claim 3, characterized in that: At the same time, the added Sr content was 0.02wt.% and the cooling rate was 2°C / s.

5. A method for improving the elongation of high iron content A356 alloy, characterized in that The following steps are involved: Step 1, preparation of Al-7Si-0.3Mg-0.5Fe alloy melt, with Al-7Si-0.3Mg alloy and Al-20Fe alloy satisfying a certain mass ratio, firstly, heating and melting the Al-7Si-0.3Mg alloy under a certain heating temperature condition to obtain an Al-7Si-0.3Mg alloy melt, referred to as AlSiMg alloy melt, then, adding Al-20Fe into the AlSiMg alloy melt and completely melting it, to obtain an Al-7Si-0.3Mg-0.5Fe alloy melt, referred to as AlSiMgFe-0.5 alloy melt; Step 2, preparation of Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy, first, the AlSiMgFe-0.5 alloy melt obtained in step 1 is cooled to a certain temperature in the furnace, then Al-10Sr is added to the AlSiMgFe-0.5 alloy melt to meet a certain addition amount of Al-10Sr, to obtain Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy melt, referred to as AlSiMgFeSr-0.5 alloy melt, then, under certain conditions, The AlSiMgFeSr-0.5 alloy melt is kept warm, and then, under certain conditions, high-purity argon gas is introduced into the AlSiMgFeSr-0.5 alloy melt. At the same time, the mold is preheated. Finally, the AlSiMgFeSr-0.5 alloy melt is cast into the mold, and the AlSiMgFeSr-0.5 alloy melt is cooled at a certain cooling rate to obtain Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy, referred to as AlSiMgFeSr-0.5 for short.

6. The method according to claim 5, characterized in that: In the step 1, the mass ratio of the Al-7Si-0.3Mg alloy to the Al-20Fe alloy is 1:0.026, and the heating temperature for obtaining the Al-7Si-0.3Mg alloy melt is 800°C.

7. The method according to claim 5, characterized in that: In the step 2, the temperature of the Al-7Si-0.3Mg-0.5Fe-0.02Sr alloy melt is 740° C., and the conditions for the introduction of high-purity argon gas are: aeration rate of 0.25 L / min, and aeration time of 3 min.

8. The method according to claim 7, characterized in that :: In the step 2, the addition amount of Al-10Sr is 0.2wt.%, the insulation temperature is 740°C, and the insulation time is 40min; The cooling rate is 2°C / s.

9. The method according to claim 8, characterized in that: The method for achieving a cooling rate of 2°C / s is that the preheating temperature of the mold is 400°C.

10. The preparation method according to claim 5, characterized in that: In the obtained high iron content A356 alloy, the length of eutectic Si is 20.00 μm, the length of Fe-rich phase is 55.70 μm; and the elongation of the alloy is 6.02%.

Citation Information

Cited By

  • Method for improving mechanical property of nickel-containing Al-Si alloy by adjusting cooling rate

    CN121637817A